Kajian Ketersediaan Pupuk Bersubsidi dan Harga Pupuk Terhadap Produksi Padi Sawah di Kabupaten Batubara - Tanjung, Yayan Noviandi Ananda; Lubis, Yusniar; Lubis, Syaifuddin (AGRISAINS: Jurnal Ilmiah Magister Agribisnis, 2020)
Paddy rice production needs to be improved because rice is the staple food of the community. Batu Bara Regency is one of the rice granaries in North Sumatra so it is very important to make various efforts to increase rice production. Among the factors that can increase rice production are the availability of subsidized fertilizer and the price of subsidized fertilizer according to the Highest Retail Price (HET).The main purpose of this study is to determine the effect of subsidized fertilizer availability and the price of subsidized fertilizer in accordance with the Highest Retail Price (HET) on paddy rice production in Batu Bara Regency. The research method is quantitative method with 100 respondents of rice farmers in Batu Bara Regency.Based on the results of the research, it is known that the availability and price of subsidized fertilizer simultaneously and partially have a significantly effect on the production of lowland rice in the Batubara Regency. The effect of variation in availability and price of subsidized fertilizer on rice production is 66.7%..The availability of subsidized fertilizer at Batubara Regency is 94.56%. Partially, the availability of subsidized fertilizer has a negative effect on the production of lowland rice in the Batubara Regency. The condition is caused by some farmers who get subsidized fertilizer more than needed. The price of subsidized fertilizer partially has a positive effect on paddy rice production, meaning that the price of subsidized fertilizer is still in the level of farmers' abilityÂ